Chapter Il socialismo liberale: Carlo Rosselli - Ghiandelli, Enno (Studi e saggi, 2021)
In order to investigate issues somehow neglected, the paper tries to carefully outline both the economic and institutional aspect and the origins and development of the Florentine anti-fascist thought. Much has been written about Carlo Rosselli's liberal socialism; still interpretations are often based more on subjective views than on in-depth studies, and this is especially true when it is the current political situation which tries to interpret Rosselli's thought. Several scholars approached Carlo Rosselli's thought assuming that the adjective 'liberal' can be translated as 'liberalistic', that the noun 'socialist' can be replaced with 'welfare' (of a moderate sort in addition), and finally that the State he theorized proves little interventionist in social and economic life; but this does not seem to be a correct interpretative key.